The Second Physical Therapy Summit on Global Health: developing an action plan to promote health in daily practice and reduce the burden of non-communicable diseases. (May 2014) - Dean, Elizabeth; Dornelas de Andrade, Armele; O'Donoghue, Grainne; Skinner, Margot; Umereh, Gloria; Beenen, Paul; Cleaver, Shaun; Afzalzada, DelAfroze; Fran Delaune, Mary; Footer, Cheryl; Gannotti, Mary; Gappmaier, Ed; et al.
Abstract Based on indicators that emerged from The First Physical Therapy Summit on Global Health (2007), the Second Summit (2011) identified themes to inform a global physical therapy action plan to integrate health promotion into practice across the World Confederation for Physical Therapy (WCPT) regions. Working questions were: (1) how well is health promotion implemented within physical therapy practice; and (2) how might this be improved across five target audiences (i.e. physical therapist practitioners, educators, researchers, professional body representatives, and government liaisons/consultants). In structured facilitated sessions, Summit representatives (n = 32) discussed: (1) within WCPT regions, what is working and the challenges; and (2) across WCPT regions, what are potential directions using World CaféTM methodology. Commonalities outweighed differences with respect to strategies to advance health-focused physical therapy as a clinical competency across regions and within target audiences. Participants agreed that health-focused practice is a professional priority, and a strategic action plan was needed to develop it as a clinical competency. The action plan and recommendations largely paralleled the principles and objectives of the World Health Organization's non-communicable diseases action plan. A third Summit planned for 2015 will provide a mechanism for follow-up to evaluate progress in integrating health-focused physical therapy within the profession.